Plant hyperaccumulators: a state-of-the-art review on mechanism of heavy metal transport and sequestration - Bhat, Basharat Ahmad; Rather, Muneeb Ahmad; Bilal, Tanveer; Nazir, Romaan; Qadir, Roof Ul; Mir, Rakeeb Ahmad (Frontiers in Plant Science, 2025)
Soils contaminated with heavy metals (HMs) pose severe consequences to living organisms, primarily affecting human health. During the past two decades, researchers have focused on hyperaccumulator plant species to augment the cleanup efforts of contaminated soils. Plants are continually exposed to HMs in the environment since they are sessile organisms. Plants that do not hyperaccumulate metals are vulnerable to high metal concentrations. Their root vacuoles create complexes with metal ligands as a detoxifying approach. On the other hand, metal-hyperaccumulating plants have evolved internal regulatory systems that allow them to hyperaccumulate excess HMs in their above-ground tissues. Unlike metal non-hyperaccumulators, they have the unusual ability to successfully carry out regular physiological activities without displaying any evident stress signs. The capacity of hyperaccumulators to acquire extra metals is due to the overexpression of constitutive metal transporter and their translocation capacity. To accomplish this, plants respond to HMs stress by inducing specifying key genes and enzymes involved in HMs chelation and compartmentalization in plants, such as phytochelatin synthases (PCS), which synthesize phytochelatins for metal binding, and metallothionein’s (MTs), which also participate in metal detoxification. Additionally, transporters like ATP-binding cassette (ABC) transporters, natural resistance-associated macrophage proteins (NRAMPs), and heavy metal ATPases (HMAs) facilitate metal sequestration into vacuoles or apoplasts. Genes encoding these proteins (e.g., PCS1, MT1/2, HMA3/4, and NRAMP3/4) are often upregulated under heavy metal stress, enabling plants to mitigate toxicity through chelation and compartmentalization. The current review provides an updated overview of major hyperaccumulator plants, explores insights into metal ion transporters and their expression patterns, and discusses the possible molecular mechanisms underlying metal ion hyperaccumulation. In addition, the evolution of various metal ion transporters and their tissue-specific expression patterns have been documented.